2021
DOI: 10.1111/jop.13256
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of methyltransferase‐like 3 and 14 in oral squamous cell carcinoma

Abstract: Objectives: This study aimed to determine expressions of methyltransferase-like 3 (METTL3) and METTL14, two enzymes essential for mRNA methylation at the adenosine (m 6 A), in oral squamous cell carcinoma (OSCC) and to investigate in vitro aggressiveness of their aberrant expressions. Methods: METTL3 and METTL14 expressions in 50 OSCC and 11 normal oral tissues were examined by immunohistochemistry. METTL3 and METTL14 expressions and m 6 A amounts were determined in three OSCC cell lines, including HN5, HN6, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
1
11
1
Order By: Relevance
“…192 , 193 Furthermore, the combined effect of METTL3 and METTL14 on oral squamous cell carcinoma was studied. 194 Moreover, in addition to the several types of RNA modifications discovered to date, there must be other RNA modifications that have not been discovered. Therefore, developing more advanced and accurate tools for determining RNA modifications is crucial to explore further the role of RNA modifications at different stages of tumor development and discover new RNA modifications.…”
Section: Discussionmentioning
confidence: 99%
“…192 , 193 Furthermore, the combined effect of METTL3 and METTL14 on oral squamous cell carcinoma was studied. 194 Moreover, in addition to the several types of RNA modifications discovered to date, there must be other RNA modifications that have not been discovered. Therefore, developing more advanced and accurate tools for determining RNA modifications is crucial to explore further the role of RNA modifications at different stages of tumor development and discover new RNA modifications.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between METTL3 expression levels and prognosis has been examined in different types of human cancer (47)(48)(49)(50). METTL3 was shown to be downregulated in glioma tissues, and the downregulation of METTL3 was shown to stimulate the malignant development of glioma (51).…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17] These studies suggested that METTL3 could promote the proliferation and migration of OSCC cells in vitro and tumor growth in vivo. [14][15][16][17] However, there are limited data on the role of METTL3 in oral precancerous lesions, especially in oral epithelial dysplasia (OED).…”
Section: Introductionmentioning
confidence: 94%